Meio ambiente e desenvolvimento: a construção do debate ambiental em O Correio da UNESCO (1972-1992) - Peguim, Cássia Natanie [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
We have observed that over the last four decades of the twentieth century, the formulation of environmental issues has emerged as a cause and symptom of a state of mind marked by the questioning of economic growth and the use of natural resources. Revealing a temporal and conceptual review process of human actions on nature, which incorporates the inconclusive debate about environment and development. In this paper we seek to elaborate on the debate that the magazine The UNESCO Courier proposes on these topics between 1972 - the year of the beginning of the publication of the magazine in Portuguese and the United Nations Conference on the Human Environment; and 1992 - the year of the United Nations Conference on Environment and Development. The discussions included in this magazine are studied from the perspective of Environmental History, particularly about the perception of the process of appropriation/transformation/destruction of the natural world over time. The magazine The UNESCO Courier contains articles that disclose and discuss the programs that United Nations of the Education, Science and Culture Organization - UNESCO had developed to address environmental issues in the areas of water resources, ocean research, conservation of the environment and natural heritage safeguarding. These programs were based on the ideal of the information exchange and scientific cooperation. Thus the magazine, conceived as a window for the world, is presented as a space of free information flow whereby UNESCO itself and its Member States express their perceptions about the environment. Perceptions pervaded by utilitarianism and validity of natural resources to promote development. Concept that The UNESCO Courier presents with continuous readings and displacements, but linked to UNESCO's ability to catalyze the demands of the Member States and to foster initiatives directed towards science and technology in...

Observamos que ao longo das últimas quatro décadas do século XX, a formulação da questão ambiental emergiu como causa e sintoma de um estado de espírito marcado pelo questionamento das modalidades do crescimento econômico e usos dos recursos naturais. Revelando um processo de revisão temporal e conceitual das ações humanas sobre a natureza, no qual se insere a inconclusão do debate sobre meio ambiente e desenvolvimento. No presente texto buscamos dissertar a respeito do debate que a revista O Correio da UNESCO comporta acerca destes temas, entre 1972 - ano do início da publicação da revista em língua portuguesa e da Conferência das Nações Unidas sobre o Meio Ambiente Humano; e 1992 - ano da Conferência das Nações Unidas sobre Meio Ambiente e Desenvolvimento. As discussões presentes na revista são problematizadas sob a perspectiva da História Ambiental, particularmente sobre a percepção do processo de apropriação/transformação/destruição do mundo natural ao longo do tempo. A revista O Correio da UNESCO comporta em suas páginas artigos que divulgam e problematizam os programas que a Organização das Nações Unidas para a Educação, a Ciência e a Cultura - UNESCO elaborara para a abordagem das questões ambientais nas áreas de recursos hídricos, pesquisas oceânicas, conservação do meio ambiente e salvaguarda do patrimônio natural. Estes programas se pautavam no ideal do intercâmbio de informações e cooperação científica. Assim, a revista, concebida como uma janela aberta para o mundo, se apresenta como espaço de livre fluxo de informações por meio do qual a própria UNESCO e seus Estados-membros expressam suas percepções sobre o meio ambiente. Percepções perpassadas pela utilidade e validade dos recursos naturais para a promoção do desenvolvimento. Conceito que em O Correio da UNESCO apresenta-se com contínuas releituras e deslocamentos...
Keywords: História ambiental; Meio ambiente; Desenvolvimento economico - Aspectos ambientais; Periódicos; Human ecology - History